Use of a microvascular anastomotic coupler device for kidney transplantation in rats - Henrik Lauer; Jana Ritter; Patrick Nachtnebel; Kathrin Simmendinger; Emily Lerchbaumer; Vladyslav Kavaka; Dominik Steiner; Jonas Kolbenschlag; Adrien Daigeler; Johannes C. Heinzel (Surgery Open Science)
Background: Allogenic kidney transplantation has been the gold standard treatment for end-stage renal disease. In the research setting, rat models are widely utilized to refine surgical techniques and enhance graft viability. One critical factor affecting transplantation outcomes is the efficiency of the venous anastomosis. This study evaluates the utility of a microvascular coupling device for venous anastomosis in a rat kidney transplantation model. Material and methods: Experimental allogenic kidney transplantations were conducted in male Brown Norway rats (n = 10) as donors and Lewis rats as recipients (n = 17), housed according to institutional guidelines. A microvascular coupling device was used for renal venous anastomosis, and creatinine levels were measured postoperatively to assess kidney function. Procedure times, ischemia duration, and postoperative complications were recorded and analyzed. Results: The venous anastomosis time averaged 6.6 ± 2.2 min. Total ischemia time averaged 42.4 ± 4.9 min. Early postoperative serum creatinine levels were slightly elevated about references thresholds, which normalized by postoperative day 3. Four animals died after successful transplantation due to urethral complications and postrenal failure (23.5 %). Other postoperative mortality was primarily linked to complications unrelated to thrombosis (n = 3, 17.6 %). Conclusion: The use of a microvascular coupling device for venous anastomosis in rat kidney transplantation significantly reduces procedure time and ischemia duration, contributing to more consistent graft outcomes. The simplification of the venous anastomosis process and reduced operative time justify the use of coupling devices. This technique holds promise for advancing preclinical transplant research and improving reproducibility in microsurgical procedures.